ANALYSIS OF ASWAJA'S DAKWAH STRATEGY IN THE ERA OF TECHNOLOGICAL DESTRUCTION DURING THE PANDEMIC - Dwi Cahyo Utomo (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study discusses the Islamic Islamic Boarding School-Based Digital Da'wah Strategy during the Pandemic (a case study of the Nurul Jadid Islamic boarding school youtube channel). The background of this research is the Covid-19 pandemic period which has a broad impact on da'wah and education, Education and da'wah programs must continue to run, YouTube social media as a strategy for preaching and broadcasting Islamic values. So in this study, 3 (three) problem formulations were formulated, namely how is the propaganda strategy for the Nurul Jadid Islamic boarding school youtube channel in presenting its da'wah content during the pandemic? What is the da'wah strategy for the YouTube channel of Pondok Pesantren Nurul Jadid in presenting its da'wah content during the pandemic? What is the Islamic boarding school-based digital preaching strategy during the pandemic? The purpose of this research is to find out what strategy is used by the youtube channel of Pondok Nurul Jadid in presenting their da'wah content. This study uses a qualitative approach. In this study, researchers used data collection methods through interviews and documentation. The interview method was carried out to find out and complete the data and efforts to obtain accurate data and appropriate data sources. In this study, the authors interviewed two informants, namely the YouTube manager of Islamic